Light controls edge functional groups to enhance membrane permeability - Sun, Tingyu; Wang, Lei; Hu, Rengkai; Li, Yangmei; Zhu, Zhi (Frontiers in Physics, 2023)
Functionalized membranes have high potential value in a broad range of practical applications, and the functional groups at the membrane edge play a vital role in the permeability of the membranes. Here, based on an edge-functionalized graphene oxide (GO) membrane model, we theoretically report that high-frequency terahertz stimulation at the frequency near 44.0 THz can significantly enhance the water permeability of the membrane by nearly five times. Its mechanism was revealed to be that the stimulation amplified the C-O stretching of the functional groups and suppressed other vibration modes of the groups. As a result, the modulation of edge functional groups brings down the energy barricade of the membrane and allows water molecules to penetrate the GO membrane more easily. These findings provide a new perspective for enhancing membrane permeability by modulating particular functional groups such as the carboxyl on the edge of the GO membrane.